Critics on postoperative functional outcomes in patients with highly migrated cervical disc prolapse - Ehsan, Meshaim; Anwar, Isma; Younas, Muhammad; Iqbal, Aman (Nepal Journal of Neuroscience, 2025)
This letter to the editor critiques the study “Postoperative Functional Outcomes in Patients with Highly Migrated Cervical Disc Prolapse” by Periyasamy et al., highlighting its contributions and limitations. While the study provides valuable insights into a rare and complex spinal condition and supports anterior cervical corpectomy and fusion (ACCF) as a treatment option, several methodological issues are noted. These include the small retrospective sample, absence of a comparative surgical arm, omission of patient-reported outcome measures, insufficient follow-up for late complications, and lack of subgroup analysis. Additionally, minimally invasive alternatives receive limited discussion despite potential advantages. The letter emphasizes the need for prospective, controlled studies incorporating PROMs, stratified analyses, and extended follow-up to better define optimal surgical strategies for highly migrated cervical disc prolapse.